Scalable production of visible light photocatalysts with extended nanojunctions of WO3/g-C3N4 using zeta potential and phase control in sol-gel process - Won, Jong Ho; Kim, Mun Kyoung; Oh, Hyung-Suk; Jeong, Hyung Mo (Elsevier BV, 2023)
Semiconductor photocatalysis for water splitting is promising approach to the current energy and environmental crisis. Although heterostructure photocatalysts exhibit enhanced photoactivity, the construction of a continuous junction at the interfaces between heterogeneous substances. In this study, visible light responsive tungsten oxide/graphitic carbon nitride composite photocatalysts with extended nanojunctions (en-WO3/g-C3N4) were synthesized through a novel sol-gel process that controlled zeta potential and sol-gel phase. The rational design of porous sphere en-WO3/g-C3N4 composite photocatalyst was constructed micropores and intimate contact between WO3 nanoparticles (NPs) and 2-dimensional (2D) g-C3N4 platelet interface. The en-WO3/g-C3N4 com-posite photocatalyst exhibited improved UV-vis absorbance and reduced recombination rate of photogenerated electron-hole pairs. The photocatalytic activity of hydrogen production was significantly enhanced by facile mass transfer and efficient charge-carrier separation due to direct Z-scheme mechanism. As a result, the hydrogen (H2) production of optimal en-WO3/g-C3N4 photocatalyst was obtained as much as 1060 mu mol h-1g-1 which is 3.8-folds higher than g-C3N4 photocatalyst (281 mu mol h-1g-1). Also, the designed en-WO3/g-C3N4 showed good stability for H2 production for 12 h under visible light irradiation.